PATOFISIOLOGI GASTROPATI NSAID - Salomo Garda Utama Simanjuntak; Jekson Martiar Siahaan (Universitas Methodist Indonesia, 2018)
NSAIDs are first line therapy for arthritis and widely used in cases of trauma, postoperative pain and other aches. But in the use of NSAID drugs whether it is needed as an analgesic or as an anti-inflammatory all have more or less side effects on the gastrointestinal. The occurrence of side effects of NSAIDs on the gastrointestinal tract can be caused by the direct toxic effects of NSAIDs on the gastric mucosa so the mucosa becomes damaged. While the systemic effect is due to the ability of NSAIDs to inhibit the work of COX-1 which catalyzes the formation of prostaglandins. Prostaglandins in the gastrointestinal mucosa function to maintain mucosal integrity, regulate blood flow, mucous secretion, bicarbonate, epithelial proliferation, and mucosal resistance to damage. The clinical spectrum of NSAID gastropathy includes a wide range of clinical conditions, ranging from the mildest form of gastrointestinal discontrol. Endoscopically mucous congestion will occur, small erosions sometimes accompanied by bleeding